Comparison of speed, agility and power between forwards and backlines among UiTM Pahang rugby player / Muhammad Syafiq Safruddin - Safruddin, Muhammad Syafiq (Faculty of Sport Science and Recreation, 2019)
The purpose of this study is to compare speed, agility and power between forwards and backlines among rugby players. A total forty subject (N=40) from Uitm Pahang Rugby Players, were selected through purposive sampling. The study was using an ex post facto design to conduct this study. The study compared of the result of post-test of30 meters sprint speed test, Illinois agility test and standing long jump test. All subject will perform only two trials for each test. They will perform for speed in the first day. The next day, they will perform a power and agility test. This study used an independent sample T-test for data analysis. There is significant difference of hypotheses testing for the 30 meter sprint speed test which is forward (M=0.520, SD=0.411) and backline (M=0.484, SD=O.215); t(40)=3.503, (p=O.OO). Hypotheses testing for Illinois agility test which is forward (M=18.33, SD=O.828) and backline (M=16.55, SD=O.634); t(40)=7.640, (p=O.OOO). The last hypotheses testing for standing long jump test which is forward (M=1.923, SD=0.486) and backline (M=2.449, SD=0.208); t (40)=-4.448, (p=0.000). To conclude, this finding suggest that backlines have greater fitness component in term of speed, agility and power than forwards.